2017
DOI: 10.1021/jacs.7b10154
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Cyclopropanation by Myoglobin Reconstituted with Iron Porphycene: Acceleration of Catalysis due to Rapid Formation of the Carbene Species

Abstract: Myoglobin reconstituted with iron porphycene catalyzes the cyclopropanation of styrene with ethyl diazoacetate. Compared to native myoglobin, the reconstituted protein significantly accelerates the catalytic reaction and the k/K value is 26-fold enhanced. Mechanistic studies indicate that the reaction of the reconstituted protein with ethyl diazoacetate is 615-fold faster than that of native myoglobin. The metallocarbene species reacts with styrene with the apparent second-order kinetic constant of 28 mM s at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(68 citation statements)
references
References 29 publications
1
67
0
Order By: Relevance
“…These enzymes have proven amenable to optimization by both genetic methods and co‐factor replacement 14, 15, 16, 17, 18, 19, 20. A common feature of these (designed) heme enzymes is that they contain a large hydrophobic substrate binding pocket orthogonal to the plane of the heme moiety.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These enzymes have proven amenable to optimization by both genetic methods and co‐factor replacement 14, 15, 16, 17, 18, 19, 20. A common feature of these (designed) heme enzymes is that they contain a large hydrophobic substrate binding pocket orthogonal to the plane of the heme moiety.…”
mentioning
confidence: 99%
“…[13] These enzymes have proven amenable to optimization by both genetic methods and co-factor replacement. [14][15][16][17][18][19][20] Ac ommon feature of these (designed) heme enzymes is that they contain al arge hydrophobic substrate binding pocket orthogonal to the plane of the heme moiety. Alternatively,s ignificant effort has been devoted to the de novo design of heme proteins,particularly based on 4-helix bundles, [21][22][23][24][25] antibodies,o ro ther proteins, [26,27] yet none of these has found application in catalysis of new-to-nature reactions.Akey difference is that these artificial heme enzymes generally do not present ad efined binding site suitable for binding the often hydrophobic substrates.H ere, we report an ovel artificial heme enzyme based on the lactococcal multidrug resistance regulator (LmrR), which is capable of catalyzing abiological enantioselective cyclopropanation reactions.Moreover,wepropose that the structural dynamics of the artificial heme enzyme are key to its catalytic activity.…”
mentioning
confidence: 99%
“…Under identical conditions to the reactions described above for C45, we confirmed that both proteins catalyze the cyclopropanation of styrene, with Mb(H64V,V68A) exhibiting >99% ee for the (S,S) product (yield = 95.9%, TTN = 959, TOF = 7.99 min -1 ) as per the literature 25 , and Rma-TDE exhibiting 70.6% ee for the (R,R) product (yield = 73.5%, TTN = 735, TOF = 6.12 min -1 ). While the yield from the C45-catalysed reaction (80.2%) does not surpass that of Mb(H64V,V68A), it is among the highest yields observed for the catalytic cyclopropanation of styrene by EDA, surpassing those exhibited by almost all reported P450 19,[25][26][27][28][29] and LmrR 24 variants, as well as several engineered myoglobins 23,25,29 . In addition, Rma-TDE exhibits a relatively high yield and enantioselectivity for styrene cyclopropanation despite being engineered for carbene insertion into Si-H bonds.…”
Section: Resultsmentioning
confidence: 97%
“…[8] Although methane generation by F430 and its model complexes were demonstrated, [14][15][16][17] much stronger reductants,s uch as Ti III citrate and Na amalgam, were found to be required relative to the thiol-based reductant employed by native MCR. [22][23][24] Thep resent study demonstrates methane generation by the Ni(TDHC) complex within aM bm atrix using amild reductant (Figure 1b). [19,20] In support of our strategy,aNisubstituted vitamin B12 derivative has been recently reported as amodel with spectroscopic characteristics similar to those of F430.…”
mentioning
confidence: 98%
“…[21] Furthermore,w eh ave focused on the protein matrix effect on physicochemical properties and reactivities of the metal-cofactor models.F or example,myoglobin (Mb), an oxygen-binding hemoprotein, is found to provide asimple and useful scaffold for ah ydrophobic cofactor-binding cavity. [22][23][24] Thep resent study demonstrates methane generation by the Ni(TDHC) complex within aM bm atrix using amild reductant ( Figure 1b). Ni(TDHC) was synthesized by cyclization of the corresponding biladiene-a,c dihydrobromide derivative in the presence of Ni(OAc) 2 .…”
mentioning
confidence: 98%